Attractions and barriers to Australian physician‐researcher careers. Issue 2 (12th February 2019) - Mills, Joanna M. Z.; Januszewski, Andrzej S.; Robinson, Bruce G.; Traill, Caroline L.; Jenkins, Alicia J.; Keech, Anthony C.
Abstract: Background: There is a global concern that physician‐researchers are 'a dying breed'. Recent studies of clinical career choices of Australian medical students and doctors have signalled the rising age of medical graduates, generational shifts in work–life attitudes and increased proportion of female graduates. There are scant data regarding Australian physician‐researchers. Aims: To develop and utilise a questionnaire determining respondent characteristics and 'push' and 'pull' factors for medical graduates to incorporate research into their careers. Methods: We developed and administered an 88‐item online survey, including quantitative and qualitative questions, to medical students, faculty and alumni of Sydney Medical School, The University of Sydney, asking about their medical career, research experience and interest and reasons for doing or not doing medical research. Responses to all 74 quantitative questions are reported here. Results: Data from 427 respondents (44% female; mean ± standard deviation age 38 ± 13 years; 56% completed or undertaking a PhD) were analysed. Attractions of research included a desire to improve human health, intellectual stimulation and career diversity. Barriers included low funding rates, job insecurity and low salaries. Although few were prepared to undertake or recommend full‐time research, 71% would recommend part‐time research. Respondents perceived a smaller‐than‐actual gap between clinical and research salaries, and if comparable (75–100% of a clinician's) salaries were available, 89% would like to spend 21–60% of their work time undertaking research. Conclusion: Many Australian medical students and doctors are interested in research, especially part time. Perceived obstacles include job insecurity, low funding rates and salary. Respondents underestimated clinical and research salary differences.